2011
DOI: 10.1021/ol201902y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Absolute Configuration Using Kinetic Resolution Catalysts

Abstract: A new method was developed to assign the absolute configuration of molecules using kinetic resolution catalysts. Secondary alcohols were acylated in the presence of Birman’s S-HBTM and R-HBTM catalysts, and the fast reacting catalyst was identified by NMR analysis of the reaction mixture. A mnemonic was developed to assign configuration based on the identity of the fast-reacting catalyst. The method uses only 1–3 mg of alcohol, and it is more convenient than the Mosher method. The kinetic resolution strategy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 42 publications
0
39
0
Order By: Relevance
“…have developed a method of assigning the absolute configuration of enantiomerically pure secondary alcohols by comparing the relative rates of acylation using both (R) and (S)-HBTM (30) as catalysts. 30 Further substitutions to the HBTM (30) core by Birman et al 31 and Smith et al 32 BTM (62) was also shown to be capable of catalysing the dynamic kinetic resolution of azlactones (66) to form -amino acid derivatives (69) in high yields and good ee (Scheme 12). 36 The highest levels of enantioselectivity were observed using di(1-naphthyl)methanol as a nucleophile, which was rationalised by the increased steric demand of the alcohol and increased - interactions with the catalyst.…”
Section: Kinetic Resolutionsmentioning
confidence: 99%
“…have developed a method of assigning the absolute configuration of enantiomerically pure secondary alcohols by comparing the relative rates of acylation using both (R) and (S)-HBTM (30) as catalysts. 30 Further substitutions to the HBTM (30) core by Birman et al 31 and Smith et al 32 BTM (62) was also shown to be capable of catalysing the dynamic kinetic resolution of azlactones (66) to form -amino acid derivatives (69) in high yields and good ee (Scheme 12). 36 The highest levels of enantioselectivity were observed using di(1-naphthyl)methanol as a nucleophile, which was rationalised by the increased steric demand of the alcohol and increased - interactions with the catalyst.…”
Section: Kinetic Resolutionsmentioning
confidence: 99%
“…1820 A mnemonic then confirms the absolute configuration based on the fast reacting enantiomer of the kinetic resolution reagent. The method is a modern implementation of the Horeau method.…”
mentioning
confidence: 69%
“…The CEC method has been applied to determine the absolute configuration of secondary alcohols, 8 lactams, 9 oxazolidinones, 9 primary amines, 10 and amino acid derivatives 11 by using Birman's HBTM acylation catalysts, 8a,b,9 DMAP catalysts,8c Mioskowski's acylating reagent 10 and molecularly imprinted polymers of DuoMIPs. The relative reaction rates of an optically pure substrate with an enantiomeric pair of catalysts are measured by 1 H NMR and the difference between the two reactions identifies the fast-reacting catalyst.…”
Section: Introductionmentioning
confidence: 99%